Eigenvalue problems with unbalanced growth: Nonlinear patterns and standing wave solutions. (November 2019) - Faragó, István; Repovš, Dušan
Abstract: We consider two classes of nonlinear eigenvalue problems with double-phase energy and lack of compactness. We establish existence and non-existence results and related properties of solutions. Our analysis combines variational methods with the generalized Pucci–Serrin maximum principle.